Problematika Peserta Didik Dalam Pembelajaran Pendidikan Agama Islam Secara Daring Pada Masa Pandemi Covid-19 di SMP Negeri 2 Kledung Kabupaten Temanggung - Sulistiyo, Rochman; Ikhrom, Ikhrom; wahib, Abdul (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study discusses the problems of students in online PAI learning. The change from face-to-face learning to online learning is quite difficult to implement. In line with this, this research asks three questions, namely: What are the problems of students in online PAI learning, what factors are behind the various problems of students and what are the implications of the problematics of online PAI learning for students. This research is a field research (field research) with a descriptive approach, data acquisition through: observation, interview, documentation. The results obtained from this study are: the problems of students in online PAI learning, namely: infrastructure problems, namely: Difficulty buying quota packages, internet network constraints, and device availability constraints, structural problems, namely: Difficulty understanding subject matter, lack of parental support, problems culture, namely: difficulty adapting, difficulty using learning applications. The factors behind the students' problems are: Lack of Digital Literacy, Lack of interaction between teachers and students, Uneven distribution of the internet network in the territory of Indonesia, Economic factors of parents, unstable self-regulation, human resource factors of parents. Implications of the Problems of Learning PAI online during a pandemi for students have an impact on: understanding, attitudes and behavior of students.